2007
DOI: 10.1200/jco.2006.08.6397
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Outcome for Adolescents With Acute Lymphoblastic Leukemia Treated on Dana-Farber Cancer Institute Acute Lymphoblastic Leukemia Consortium Protocols

Abstract: Adolescents were more likely to present at diagnosis with biologically higher risk disease (T-cell phenotype and absence of the TEL-AML1 fusion) and more likely to experience treatment-related complications than younger children. However, the 5-year EFS for older adolescents was 78% +/- 6%, which is superior to published outcomes for similarly aged patients treated with other pediatric and adult ALL regimens. Based on this experience, we currently are piloting our regimen in patients aged 18 to 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
113
4
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 23 publications
13
113
4
5
Order By: Relevance
“…Barry et al reported the outcome of adolescents treated in the Dana-Farber Cancer Institute (DFCI) ALL Consortium Protocols conducted between 1991 and 2000 (Barry et al 2007). A total of 844 patients aged 1 to 18 years, with newly diagnosed ALL were enrolled into two consecutive DFCI-ALL Consortium Protocols.…”
Section: Prospective Trials 321 Results Of the Treatment Of Adolescmentioning
confidence: 99%
“…Barry et al reported the outcome of adolescents treated in the Dana-Farber Cancer Institute (DFCI) ALL Consortium Protocols conducted between 1991 and 2000 (Barry et al 2007). A total of 844 patients aged 1 to 18 years, with newly diagnosed ALL were enrolled into two consecutive DFCI-ALL Consortium Protocols.…”
Section: Prospective Trials 321 Results Of the Treatment Of Adolescmentioning
confidence: 99%
“…A strong example of this situation is the increase in survival among children and adolescents with acute lymphoid leukemia, observed in the last decades. 8 Most data on cancer incidence available in Brazil derive from Populational Registers recently implemented, preventing the assessment of historical series. Moreover, as Doll had already emphasized years ago, in an instructive and prolonged feud with Bailar, the examination of mortality trends, rather than incidence, is more adequate to evaluate whether progress against cancer is occurring or not, since incidence data are more subject to changes in surveillance and in the very recording practices, whereas mortality statistics are based on systems of vital statistics established a longer time ago.…”
Section: Discussionmentioning
confidence: 99%
“…La intensificación del tratamiento mantuvo una baja tasa de mortalidad por toxicidad, de 6%, similar a lo observado en la literatura [15][16] . A su vez, la reciente centralización del tratamiento de las leucemias agudas en hospitales calificados y su incorporación al programa de Garantías Explícitas en Salud (GES) en julio de 2007, así como la implementación de protocolos basados en evidencia, han permitido mejorar los resultados en patologías de alta complejidad como la LLA.…”
Section: Conclusiónunclassified
“…1 encargado de Protocolo lla [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. 2 Hematóloga unidad de Hematología intensiva, Hospital del salvador.…”
unclassified